Evaluation of Morphological Characteristics of Bhutanese Landrace Chilies (Capsicum spp.) - Wangdi, Thinley; Watcharawetsaringkharn, Suthep; Philadee, Jutamat; Pooprompan, Pornpan (Thai Journal of Science and Technology, 2019)
Abstract Chili plays an integral part in a different culture. It is cultivated as commercial and in backyards for spices, vegetables, ornamental and medicinal purposes. In Bhutan, chili (Capsicum spp.) is an important crop and is cultivated across the country. Twenty chili varieties cultivated in Bhutan were collected from different chili growing regions to evaluate morphological characteristics at Maejo University, Chiang Mai, Thailand. The experiment was conducted under 50% shade net in a completely randomized design with five replications. The results showed a significant difference among the varieties, the earliest flowering was recorded from 23 to 42 days in 15 varieties and late flowering in 67 days in ‘Dhallay’ variety. The mean plant height, canopy, and stem diameter were 76.3±18.2 cm, 42.7±7.6 cm and 7.5±3.1 mm, respectively, while the mean fruit length, width and weight were 9.8±4.4 cm, 2.1±0.7 cm, and 11.1±9.6 g, respectively. The varieties ‘Tsakaling’ and ‘Indian Fat’ had purple corolla color which indicates Capsicum pubescens Ruiez. & Pav. species. Geographical group analysis showed that varieties introduced from Japan had different characters from those of the Bhutanese landrace varieties except for leaf width, plant height, plant canopy and stem diameter. The results of morphological characteristics from this study will have potential application in chili genetic diversity conservation and plant breeding program. Keywords: Chili; landrace; morphology; Bhutan